Korupsi: Menelusuri Akar Persoalan dan Menemukan Alternatif Pemecahannya - Fatimah, Siti (Jurnal Demokrasi, 2009)
Corruption is a most dangerous crime among the others. It will have social implications in society, such as social imbalance and inequality. This article will analyze some issues related to the corruption, such as why the corruption be something usual in this country (Indonesia); what factors cause someone to corrupt in this country; and what can we do to overcome the issue of corruption. This article also tries to analyze the issue of corruption in educational institution. Â  Kata kunci: Korupsi, birokrasi, kesenjangan sosial, ketidakadilan